Phylogenetic and Molecular Analysis of the Porcine Epidemic Diarrhea Virus in Mexico during the First Reported Outbreaks (2013–2017) - José Francisco Rivera-Benítez; Rebeca Martínez-Bautista; Raúl González-Martínez; Jazmín De la Luz-Armendáriz; Irma Herrera-Camacho; Nora Rosas-Murrieta; Laura Márquez-Valdelamar; Rocio Lara (Viruses, 2024)
The characteristics of the whole PEDV genome that has circulated in Mexico from the first outbreak to the present are unknown. We chose samples obtained from 2013 to 2017 and sequenced them, which enabled us to identify the genetic variation and phylogeny in the virus during the first four years that it circulated in Mexico. A 99% identity was found among the analyzed pandemic strains; however, the 1% difference affected the structure of the S glycoprotein, which is essential for the binding of the virus to the cellular receptor. The S protein induces the most efficacious antibodies; hence, these changes in structure could be implicated in the clinical antecedents of the outbreaks. Antigenic changes could also help PEDV avoid neutralization, even in the presence of previous immunity. The characterization of the complete genome enabled the identification of three circulating strains that have a deletion in ORF1a, which is present in attenuated Asian vaccine strains. The phylogenetic analysis of the complete genome indicates that the first PEDV outbreaks in Mexico were caused by INDEL strains and pandemic strains related to USA strains; however, the possibility of the entry of European strains exists, which may have caused the 2015 and 2016 outbreaks.